High-sensitivity C-reactive protein in children at risk for coronary artery disease - AKALIN, FİGEN; HAKLAR, GONCAGÜL (BLACKWELL PUBLISHING, 2007)
Aim: To determine the value of high-sensitivity C-reactive protein (hs-CRP) in predicting risk factors for coronary heart disease (CHD) in children. Methods: We measured hs-CRP levels in 51 children (11.79 +/- 3.14 years) with risk factors for CHD (hypercholesterolemia, hypertension, obesity, low HDL cholesterol and familial history of CHD). The results were compared with 26 children (12.98 +/- 2.59 years) without any risk factors. Results: The children with risk factors had significantly higher serum levels of hs-CRP compared to the control group (3.33 +/- 4.58 vs. 0.92 +/- 1.90 mg/L, respectively, p < 0.01). CRP concentrations significantly increased in children with three or more risk factors. Hs-CRP levels correlated to body mass index (r = 0.411, p = 0.003), diastolic blood pressure (r = 0.323, p = 0.021), fibrinogen (r = 0.447 and p = 0.004) and HDL cholesterol levels (r = -0.461 and p = 0.001). Cutoff value for CRP was 1.04 mg/L with 58% sensitivity and 92% specificity. Conclusion: Serum hs-CRP level is a useful marker in screening the children who are under the risk of CHD in adulthood. Early identification of the children with risk factors and intervention for obesity, harmful habits and life style in childhood might decrease the incidence of coronary heart disease in adulthood.
Keywords: atherosclerosis; C-reactive protein; cardiovascular disease risk factors; children; CARDIOVASCULAR-DISEASE; HEART-DISEASE; YOUNG-ADULTS; INSULIN-RESISTANCE; ATHEROSCLEROSIS; INFLAMMATION; INTERLEUKIN-6; ASSOCIATIONS; ADOLESCENTS; CHOLESTEROL